2018
DOI: 10.3390/molecules23040852
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pinocembrin Isolated from Mexican Brown Propolis on Diabetic Nephropathy

Abstract: Propolis is a resinous beehive product that has been used worldwide in traditional medicine to prevent and treat colds, wounds, rheumatism, heart disease and diabetes. Diabetic nephropathy is the final stage of renal complications caused by diabetes and for its treatment there are few alternatives. The present study aimed to determine the chemical composition of three propolis samples collected in Chihuahua, Durango and Zacatecas and to evaluate the effect of pinocembrin in a model of diabetic nephropathy in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Furthermore, studies have shown that pinocembrin can prevent kidney damage caused by diabetes, but when the kidney is damaged, pinocembrin will aggravate the organ’s condition [62]. This finding indicates that pinocembrin can be used as a preventive agent for kidney damage before injury.…”
Section: Pharmacological Effects Of Pinocembrinmentioning
confidence: 99%
“…Furthermore, studies have shown that pinocembrin can prevent kidney damage caused by diabetes, but when the kidney is damaged, pinocembrin will aggravate the organ’s condition [62]. This finding indicates that pinocembrin can be used as a preventive agent for kidney damage before injury.…”
Section: Pharmacological Effects Of Pinocembrinmentioning
confidence: 99%
“…Pinocembrin (10 mg/kg i.g. for 40 days), a marker of poplar type propolis, also lowered blood glucose, total cholesterol, LDL-C, and triglyceride levels in STZ-treated Wister rats [146].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Some biological activities have been ascribed to propolis, and they include: anti-hyperglycaemic, antioxidant, anti-inflammatory, anti-apoptotic and anti-microbial effects [13,19,20]. Others include renoprotective [21,22], cardioprotective [23,24] and hepatoprotective [25,26] effects.…”
Section: Introductionmentioning
confidence: 99%